Peran Quizizz sebagai Media Pembelajaran dengan Menghadirkan Fitur Menarik Bagi Siswa Jenjang SMA - Nurhalizah, Siti; Hindun, Hindun (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
Technology is developing very rapidly, so current technological developments have a big influence on human development. Currently, many educators are using technology as a learning medium that supports effective student learning, one of which is the Quizzzz application. Quizizz is used by teachers as a medium for assessing or evaluating student understanding. This research aims to determine the role of the Quizizz application as a learning medium that presents interesting features and the effectiveness of using the application. This study used the descriptive-qualitative method. The technique used in this research is listening to and recording the results of high school students' questionnaire data. The results of the research show that (1) the use of the Quizizz application as a learning medium used by teachers in assessments or evaluations to measure students' learning abilities is very effective. (2) The effectiveness of the use of the Quizizz application is appropriate and utilized to provide learning motivation for high school students. (3) The obstacle for students in using the Quizizz application is that they require a good internet connection; for this, they need an area that has a good internet connection. (4) Students' impressions and messages from using the Quizizz application, namely that the features in it attract students' attention and that it is very easy to use.